2003
DOI: 10.1046/j.1468-3083.2003.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic findings in subjects with psoriatic arthropathy

Abstract: We conclude that mild diastolic dysfunction may accompany PA but our data should be confirmed by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 7 publications
2
19
2
1
Order By: Relevance
“…It has been reported that psoriasis may accompany mild diastolic dysfunction [35]. Although we could not find a significant association between frequency of diastolic function and PWD and QTcD, still there may be a possible contribution of diastolic dysfunction parameters to the increased PWD in psoriasis.…”
Section: Discussioncontrasting
confidence: 83%
“…It has been reported that psoriasis may accompany mild diastolic dysfunction [35]. Although we could not find a significant association between frequency of diastolic function and PWD and QTcD, still there may be a possible contribution of diastolic dysfunction parameters to the increased PWD in psoriasis.…”
Section: Discussioncontrasting
confidence: 83%
“…Aortic incompetence was reported in less than 4%. Other cardiac involvement, including subtle atrioventricular nodal involvement and diastolic dysfunction, was reported from case-control studies in Israel and Turkey [24,25]. A larger study in Spain, however, did not find echocardiographic abnormalities in PsA patients as compared with healthy controls [26].…”
Section: Clinical Manifestation Of Psoriatic Arthritismentioning
confidence: 88%
“…reported comparable LV dimensions, wall thickness, and EF between psoriasis and healthy subjects. Saricaoglu et al . investigated 21 PsA patients with LV EF of >50% and reported increased LV end‐diastolic and end‐systolic diameters compared with those in control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that psoriasis does not impair left ventricular (LV) systolic function . However, one publication has revealed subclinical LV dysfunction to be more frequent in psoriatic arthritis (PsA) .…”
Section: Introductionmentioning
confidence: 99%